The role of carotenoids in the modulation of physiochemical aspects that determine Staphylococcus aureus survival under desiccation (2023)
Staphylococcus aureus (S.aureus) is a bacterial species that exhibits a golden coloration, given by the triterpenoid carotenoid staphyloxanthin. It is present on the skin or mucous of 20% to 30% of the human population in its natural bacterial flora, but it is also an opportunistic pathogen and one of the principal causes skin infections, myocarditis, transplant induced infections, and other nosocomial infections, that range from minor to life threatening diseases. In United States in 2017 more than 119 thousand people suffered from bloodstream S.aureus infections and nearly 20 thousand died from this condition. These numbers represent the equivalent yearly deaths induced by HIV, tuberculosis and hepatitis combined. It is also the second global cause of blood infections, and one of the principal food poisoning vectors. The incidence of these infections varies depending on the socioeconomic and legislative public health situation of each country, the population, and the health system. Also, certain groups have higher incidence such as: immuno-compromised patients and implant users. S.aureus is highly tolerant to desiccation based on its adaptability and protection mechanisms, such as the production of the molecule staphyloxanthin (STX), a membrane-bound carotenoid, that has been demonstrated to mediate fluidity on the membrane and provide antioxidant properties. The study of desiccation resistance factors such as staphyloxanthin and its ability to protect the cell by altering physically the cell membrane, can provide insight for future solutions to minimize the impact of the infections and decrease the transmissivity. This document focuses on the comparison of three strains: a) a strain that synthesizes normal levels of STX (144), b) a strain that does not synthesize carotenoids (145), and c) a strain that over-produces STX (147). We analize3 physiochemical properties (water content, cell shape, and membrane lipid packing) and 3 survival treatment experiments (normal air exposure, anaerobic conditions, and exposure to an oxidative environment induced by UV light). It was found that, after desiccation, there is a significant difference (p<0.001) between the remaining water percentage for strain the 147, with respect to 144 and 145, where 144 and 145 strains have similar remaining water percentages. Besides, there is a significant difference between the average cell area per strain (p<0.001, p<0.001, p<0.001) conserved through time, with 145 being the smallest and 147 the biggest. There is not a significant difference in size in the majority of the time points, only in 168h it can be stated that the strain didn¿t change at the same rate than the other two. We observe strong differences in the lipid phase behavior of the three strains after desiccation as evidenced from the thermotropic behavior of the CH2 asymmetric stretch wavenumber of the acyl chains. The gel to liquid-crystalline phase transition temperature shifts upwards for all the strains after desiccation, from 15 °C to 29.5, 26.5 and 24.5 °C respectively for each strain, after being desiccated, making the lipids at room temperature in gel phase. This is expected since lipids present higher packing levels in the absence of water. Also, there is an increase of the wavenumber of the normal modes of CH2, especially notable for 147, which also indicate higher packing levels. This is consistent with the previous results of water percentages and morphology that indicated higher rigidity on the membrane and less cooperativeness of 147 compared to the other strains. Meantime, 145 showed lower wavenumbers stating better membrane organization because of an increase in lipid packaging. Finally, the type of desiccation treatment had an effect on its survival, in the UV treatment the survival rate decreased one order of magnitude compared to the results obtained for the desiccation treatment in normal air conditions, while for anaerobe conditions, the same diminution of survival rate was found but 145 recovered certain survival capacity, reaching the same survival rates as the other strains. The results show that carotenoids are key in desiccation tolerance principally because they protect cells from oxidative stress.